2020
DOI: 10.1113/ep088894
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Dnmt3a ameliorates diabetic muscle atrophy by modulating the Pten/Akt pathway

Abstract: New Findings What is the central question of this study?Does Dnmt3a play a crucial role in regulating diabetic muscle atrophy? What is the main finding and its importance?Muscle atrophy is one of the major long‐term complications of diabetes mellitus. However, little is known about the molecular mechanism involved. In this paper, we demonstrated that Dnmt3a overexpression effectively improves the diabetic muscle health in mice and documented the underlying mechanisms. DNMT3A might become a promising target to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…In this study, we found that Dnmt3 (Dnmt3a and Dnmt3b), but not Dnmt1 exhibited responsive expression after CE incubation to eliminate STS-induced toxicity ( Figure 4 ). Recently, Dnmt3a was reported to improve muscle atrophy in diabetic mice by activating Akt, suggesting that Dnmt3a could provide feedback to the PI3K/Akt signaling pathway and play a role in maintaining cell survival ( Wang et al., 2020 ). Furthermore, CE-mediated recovery of CaM was impaired by 5-AZ, an inhibitor of Dnmts.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that Dnmt3 (Dnmt3a and Dnmt3b), but not Dnmt1 exhibited responsive expression after CE incubation to eliminate STS-induced toxicity ( Figure 4 ). Recently, Dnmt3a was reported to improve muscle atrophy in diabetic mice by activating Akt, suggesting that Dnmt3a could provide feedback to the PI3K/Akt signaling pathway and play a role in maintaining cell survival ( Wang et al., 2020 ). Furthermore, CE-mediated recovery of CaM was impaired by 5-AZ, an inhibitor of Dnmts.…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated that continuous administration of Dnmt3a to the tibialis anterior muscle significantly counteracted streptozotocin (STZ)-induced DM muscle atrophy and enhanced myotube formation in C2C12 myoblasts. Crucially, Dnmt3a overexpression also reinstated the expression levels of atrophy genes such as MAFbx , MuRF1 , MyoD , and Myog , both in vivo and in vitro [ 55 ].
Fig.
…”
Section: The Role Of Epigenetic In Skeletal Muscle Atrophymentioning
confidence: 99%
“…Thus, the AKT/ PTEN pathway is critical for skeletal muscle hypertrophy and prevention of muscle atrophy. 17 Our previous studies have shown that lifelong exercise-activated PTEN/AKT pathway and indirectly inhibited the HIPPO pathway activation. 18 Therefore, we investigated whether HIIT acts on HIPPO pathway to prevent muscle atrophy along with regulating AKT/PTEN pathway.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, intracellular PTEN pathway activation inhibited AKT pathway activity and induced apoptosis. Thus, the AKT/PTEN pathway is critical for skeletal muscle hypertrophy and prevention of muscle atrophy 17 . Our previous studies have shown that lifelong exercise‐activated PTEN/AKT pathway and indirectly inhibited the HIPPO pathway activation 18 .…”
Section: Introductionmentioning
confidence: 99%